Dirty Politics?: New Labour, British Democracy and the Invasion of Iraq - Coates, David (Labour / Le Travail, 2007)
The article reviews the book, "Dirty Politics? New Labour, British Democracy and the Invasion of Iraq," by Steven Kettell.
Keywords: BOOKS -- Reviews; DIRTY Politics? New Labour, British Democracy & the Invasion of Iraq (Book); KETTELL, Steven; Nonfiction; Political Science